Hepatitis E Outbreak on Cruise Ship - Said, Bengü (Centers for Disease Control and Prevention, 2009)
In 2008, acute hepatitis E infection was confirmed in 4 passengers returning to the United Kingdom after a world cruise. Epidemiologic investigation showed that of 789 persons who provided blood samples, 195 (25%) were seropositive, 33 (4%) had immunoglobulin [Ig] M levels consistent with recent acute infection (11 of these persons were symptomatic), and 162 (21%) had IgG only, consistent with past infection. Passenger mean age was 68 years. Most (426/789, 54%) passengers were female, yet most with acute infection (25/33, 76%) were male. Sequencing of RNA from 3 case-patients identified hepatitis E virus genotype 3, closely homologous to genotype 3 viruses from Europe. Significant association with acute infection was found for being male, drinking alcohol, and consuming shellfish while on board (odds ratio 4.27, 95% confidence interval 1.23–26.94, p = 0.019). This was probably a common-source foodborne outbreak.